The high-mountain species Staurophora vilamaensis N.I.Maidana, C.Seeligmann & M.R.Morales, sp. nov. (Anomoeoneidaceae, Bacillariophyta) - Maidana, Nora Irene (2023)
Staurophora Mereschkowsky, 1903, nom. cons. is a genus characteristic of marine and brackishenvironments (Bahls, 2011). It is also a notable feature of the diatom flora of the high-altitude lakesof the Central Andes (South America), which have variable salinities, and where at least threespecies have been found thus far [S. elata (Hustedt) D.G.Mann, S. wislouchii (Poretzky &Anisimova) D.G.Mann (Maidana & al., 1998, as Stauroneis wislouchii Poretzky & Anisimova]together with an undescribed species referred to as “Staurophora vilamae” in Maidana & al.(2009). This latter taxon has been found not only at the type locality (Laguna Vilama, Jujuy,Argentina, c. 4500 m asl) but also in other lakes and meadows, from oligohaline to mesohaline, innorth-western Argentina (Maidana & Seeligmann 2015) and in two lakes in Bolivia (Alvarez-Blanco & al. 2011).